Possible Association Between DHEA and PKCε in Hepatic Encephalopathy Amelioration: A Pilot Study - Di Cerbo, Alessandro; Roncati, Luca; Marini, Carlotta; Carnevale, Gianluca; Zavatti, Manuela; Avallone, Rossella; Corsi, Lorenzo (Frontiers in Veterinary Science, 2021)
Objective: Hepatic encephalopathy (HE) is a neuropsychiatric syndrome caused by liver failure and by an impaired neurotransmission and neurological function caused by hyperammonemia (HA). HE, in turn, decreases the phosphorylation of protein kinase C epsilon (PKCε), contributing to the impairment of neuronal functions. Dehydroepiandrosterone (DHEA) exerts a neuroprotective effect by increasing the GABAergic tone through GABAA receptor stimulation. Therefore, we investigated the protective effect of DHEA in an animal model of HE, and the possible modulation of PKCε expression in different brain area. Methods: Fulminant hepatic failure was induced in 18 male, Sprague–Dawley rats by i.p. administration of 3 g/kg D-galactosamine, and after 30 min, a group of animals received a subcutaneous injection of 25 mg/kg (DHEA) repeated twice a day (3 days). Exploratory behavior and general activity were evaluated 24 h and 48 h after the treatments by the open field test. Then, brain cortex and cerebellum were used for immunoblotting analysis of PKCε level. Results: DHEA administration showed a significant improvement of locomotor activity both 24 and 48 h after D-galactosamine treatment (****p < 0.0001) but did not ameliorate liver parenchymal degeneration. Western blot analysis revealed a reduced immunoreactivity of PKCε (*p < 0.05) following D-galactosamine treatment in rat cortex and cerebellum. After the addition of DHEA, PKCε increased in the cortex in comparison with the D-galactosamine-treated (***p < 0.001) and control group (*p < 0.05), but decreased in the cerebellum (*p < 0.05) with respect to the control group. PKCε decreased after treatment with NH4Cl alone and in combination with DHEA in both cerebellum and cortex (****p < 0.0001). MTS assay demonstrated the synergistic neurotoxic action of NH4Cl and glutamate pretreatment in cerebellum and cortex along with an increased cell survival after DHEA pretreatment, which was significant only in the cerebellum (*p < 0.05). Conclusion: An association between the DHEA-mediated increase of PKCε expression and the improvement of comatose symptoms was observed. PKCε activation and expression in the brain could inhibit GABA-ergic tone counteracting HE symptoms. In addition, DHEA seemed to ameliorate the symptoms of HE and to increase the expression of PKCε in cortex and cerebellum.